An Investigation into the Biomarker Potential of Highly Branched Isoprenoids in Northern Minnesota Lake Sediments (2022-03-25) - Hanson, Bennett; University of Minnesota Duluth. Department of Chemistry and Biochemistry (2022)
Friday, March 25, 2022, 3:30 p.m.; Chem 200; Bennett Hanson, Master's Student, Department of Chemistry & Biochemistry, University of Minnesota Duluth; Research Advisor: Dr. Kathryn Schreiner Highly Branched Isoprenoids (HBIs) are isoprene-based lipids synthesized by diatoms. HBIs are often used as sea-ice proxies in marine environments where certain HBIs indicate the presence of sea ice diatoms. However, few studies have focused on HBIs produced by freshwater diatoms. The goal of this study is to expand the knowledge of the types of HBIs produced in freshwater environments through the identification and quantification of HBIs in surface sediment and periphyton samples containing HBI- producing freshwater diatoms collected from small lakes, the St. Louis River estuary, and Lake Superior. Each of the seven study sites was sampled twice, once in the summer and once in the winter to determine if seasonal conditions affect HBI production of diatom communities. At each site, the entire HBI suite is characterized by gas chromatography-mass spectrometry (GC-MS) analysis of the nonpolar extractable fraction, and the genera of diatoms present are characterized by visual identification. Additionally, single strains of Nitzschia frustulum and Fragilaria capucina have been isolated and are being grown in liquid media over a range of temperatures. Eight distinct HBIs have been identified from the seven sites with concentrations ranging from 0.1-0.9 ?g g-1 dry sediment, only one of which has been previously identified in the literature. One distinct C30:6 and two distinct C30:4 HBIs have been identified from the single-strain studies.